Adaptation Strategy of Seaweed Cultivation to Face the Climate Change (Case Study in Segoro Anakan Bay Ngadirojo, Pacitan) - Amri, Syahrial Nur; Arifin, Taslim (Forum Geografi, 2016)
The damage of coastal ecosystems are no longer dominated by human activity, but the condition of global climate change were also influenced. Climate change impact on the environment influencing the coastal management paradigm. This study emphasizes on how to develop a adaptation strategy of coastal zone management due to the impact of climate change through remote sensing approach, Geographic Information Systems (GIS), and adaptation strategies analysis. Location of research conducted in the Region of Segoro Anakan Bay, District Ngadirojo Pacitan. The results showed the impact of climate change is affecting the area and production of seaweed culture in the form of tectonic conditions aggravated by silting waters. To combat the effects of climate change, the adaptation scenario is implemented to intensification and extensification of land use, alternative livelihoods, minawisata as a combination of all three.